Power quality optimization using a novel backstepping control of a three-phase grid-connected photovoltaic systems - Salwa Naddami; Najib Ababssi (International Journal of Electrical and Computer Engineering (IJECE), 2023)
A novel nonlinear backstepping controller based on direct current (DC) link voltage control is proposed in three-phase grid-connected solar photovoltaic (PV) systems to control the active and reactive power flow between the PV system and the grid with improved power quality in terms of pure sinusoidal current injection with lower total harmonic distortion (THD), as well as to ensure unity power factor, or to compensate for reactive power required by the load, i.e., the electrical grid. The output power of the PV array is supplied to the grid through a boost converter with maximum power point tracking (MPPT) control and an inverter. Simulation results of the proposed controller show good robustness under nominal conditions, parameter variations, and load disturbances, which presents the main advantage of this controller as compared to an existing controller. The performance of this work was evaluated using a MATLAB/Simulink environment.